2023
DOI: 10.3390/antibiotics12030498
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Composition Can Predict Colonization by Multidrug-Resistant Bacteria in SARS-CoV-2 Patients in Intensive Care Unit: A Pilot Study

Abstract: The SARS-CoV-2 infection has increased the number of patients entering Intensive Care Unit (ICU) facilities and antibiotic treatments. Concurrently, the multi-drug resistant bacteria (MDRB) colonization index has risen. Considering that most of these bacteria are derived from gut microbiota, the study of its composition is essential. Additionally, SARS-CoV-2 infection may promote gut dysbiosis, suggesting an effect on microbiota composition. This pilot study aims to determine bacteria biomarkers to predict MDR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Prolonged ICU stay, frequent antibiotic therapy, invasive devices, and corticosteroid use could explain, at least in part, the higher risk for BSI in COVID-19 patients [31][32][33][34]. However, a causal relationship between COVID-19 and ICU-acquired infection was suggested, and could be related to major immune dysregulation, often compared to the "cytokine storm" [35,36], post-aggressive immunoparalysis [37][38][39][40], and altered microbiota [41]. A recent large multicenter before-and-after study reported a higher risk for ICU-acquired infections related to MDRB in COVID-19 patients as compared to non-COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged ICU stay, frequent antibiotic therapy, invasive devices, and corticosteroid use could explain, at least in part, the higher risk for BSI in COVID-19 patients [31][32][33][34]. However, a causal relationship between COVID-19 and ICU-acquired infection was suggested, and could be related to major immune dysregulation, often compared to the "cytokine storm" [35,36], post-aggressive immunoparalysis [37][38][39][40], and altered microbiota [41]. A recent large multicenter before-and-after study reported a higher risk for ICU-acquired infections related to MDRB in COVID-19 patients as compared to non-COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether the alteration of microbiota results in different effects on ICU-acquired infection in COVID-19 patients, as compared with non-COVID-19 patients is still to be evaluated. In a recent pilot study performed in 17 COVID-19 patients, gut microbiota composition significantly differed between patients with ICU-acquired colonization related to MDR bacteria, compared with those with no MDR bacteria colonization [ 59 ]. Further studies are needed to confirm these findings.…”
Section: Specific Preventive Measuresmentioning
confidence: 99%
“…Of particular note, the rise in multidrug-resistant bacterial intestinal carriage drives superinfections and mortality [ 8 , 9 ], which are particularly worrisome in vulnerable populations. Recently, a Spanish pilot study showed that the gut microbiota profile can become a predictive biomarker for multidrug-resistant bacteria colonization in SARS-CoV-2 patients [ 10 ]. Among Gram-negative bacteria, Acinetobacter baumannii and Klebsiella pneumoniae have been reported as the most frequently isolated species among COVID-19 patients with hospital-acquired superinfections [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%